2015
DOI: 10.1590/1807-3107bor-2015.vol29.0029
|View full text |Cite
|
Sign up to set email alerts
|

The smear layer created by scaling and root planing is physiologically eliminated in a biphasic process

Abstract: Mechanical instrumentation of the root surface causes the formation of a smear layer, which is a physical barrier that can affect periodontal regeneration. Although different procedures have been proposed to remove the smear layer, there is no information concerning how long the smear layer persists on root surfaces after instrumentation in vivo. This study assessed the presence of the smear layer on root surfaces over a 28-day period after subgingival instrumentation with hand instruments. Fifty human teeth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…We know that the mechanical debridement done as part of periodontal therapy leaves a smear layer covering the debrided root surface. [ 1 10 ] Various chemicals like citric acid, EDTA, and tetracycline plus techniques like laser have shown successful eradication of the smear layer. [ 11 12 ] As a final endodontic irrigant to clean the canal and eliminate the smear layer, Torabinejad et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that the mechanical debridement done as part of periodontal therapy leaves a smear layer covering the debrided root surface. [ 1 10 ] Various chemicals like citric acid, EDTA, and tetracycline plus techniques like laser have shown successful eradication of the smear layer. [ 11 12 ] As a final endodontic irrigant to clean the canal and eliminate the smear layer, Torabinejad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined various chemical conditioning techniques since the possibility of periodontal regeneration could rise with the successful removal of the smear layer. [ 1 ] In practice, such smear layers over the root can be dissolved by subjecting the root to chemical treatment using agents such as citric-acid-4.25%, Ethylenediaminetetraacetic (EDTA)-17%, Tetracycline hydrochloride acid-10% and phosphoric acid-37%. After dissolving the smear layer, the collagen is exposed on the root surface, thereby facilitating the attachment of fibroblasts to the root.…”
Section: Introductionmentioning
confidence: 99%
“…who observed that after instrumentation there was a presence of a heavy smear layer, fewer fibrin network formation, or appearance of blood cells. [ 12 , 13 ] According to Matsuoka et al ., they stated that Er, Cr: YSGG laser utilized with water was successful in debris and SLR when compared to the control group (SRP). [ 14 ] The mechanism of the removal of smear layer by the Er, Cr: YSGG laser is based on the expansion and implosion of vapor lock and secondary cavitation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Subgingival mechanical instrumentation accumulates debris onto the root surfaces, also known as the smear layer ( Figure 2 a–c), which limits the spreading of specialized cells and impairs periodontal wound healing [ 86 , 92 ]. Several adjunctive subgingivally applied agents may enhance the removal of the smear layer and stimulate the colonization of specialized cells [ 77 , 93 ], thus creating the premises for the development of a new connective tissue attachment [ 86 , 92 ]. However, some products, such as citric acid, tetracycline, or EDTA, did not provide any additional clinical benefits in an attempt to regenerate an affected periodontium [ 94 ].…”
Section: The Effect Of Sulphonic/sulfuric Acids-based Antimicrobial D...mentioning
confidence: 99%